Time-Oriented Models and the Legal Process: Reducing Delay and Forecasting the Future - Stuart S. Nagel; Marian Neef (Washington University Law Quarterly, 1978)
This article describes a series of models for analyzing the legal process that emphasize either time-saving or the prediction of future events from past events.
Keywords: Administration of criminal justice; Judicial statistics